Checklist of the spiders (Araneae) of Kenya - Kioko Grace M.; Marusik Yuri M.; Li Shuqiang; Kioko Esther N.; Ji Liqiang (Pensoft Publishers, 2022)
A checklist of 805 spider species and subspecies belonging to 57 families described and/or reported from Kenya up to 31 December 2018 is provided. Species distribution within Kenya is given according to counties and specific localities. A historical survey is provided and each record is presented in its original combination. The list is dominated by members of the families Salticidae and Linyphiidae (160 and 110 species, respectively). Eighteen families are represented by a single species. About 300 species are known exclusively from Kenya and 158 species are sub-endemics. Two hundred and forty two species are described from a single sex (159 females and 83 males) and 24 from juveniles. Nairobi County has the greatest number of records, five counties had a frequency of one, while nine counties had no collection records. There are two fossil spiders known from Kenya belonging to the family Oonopidae. One new combination is proposed: Hypsosinga holzapfelae (Lessert, 1936), comb. nov. (ex. Araneus Clerck, 1757).